The Role of Astrocytic Calcium Signaling in the Aged Prefrontal Cortex - Guerra-Gomes, Sónia; Viana, João Filipe; Nascimento, Diana Sofia Marques; Correia, Joana Sofia; Sardinha, Vanessa Morais; Caetano, Inês; Sousa, Nuno; Pinto, Luísa; Oliveira, João Filipe (Frontiers in Cellular Neuroscience, 2018)
Aging is a lifelong process characterized by cognitive decline putatively due to structural and functional changes of neural circuits of the brain. Neuron-glial signaling is a fundamental component of structure and function of circuits of the brain, and yet its possible role in aging remains elusive. Significantly, neuron-glial networks of the prefrontal cortex undergo age-related alterations that can affect cognitive function, and disruption of glial calcium signaling has been linked with cognitive performance. Motivated by these observations, we explored the possible role of glia in cognition during aging, considering a mouse model where astrocytes lacked IP3R2-dependent Ca2+ signaling. Contrarily to aged wild-type animals that showed significant impairment in a two-trial place recognition task, aged IP3R2 KO mice did not. Consideration of neuronal and astrocytic cell densities in the prefrontal cortex, revealed that aged IP3R2 KO mice present decreased densities of NeuN+ neurons and increased densities of S100β+ astrocytes. Moreover, aged IP3R2 KO mice display refined dendritic trees in this region. These findings suggest a novel role for astrocytes in the aged brain. Further evaluation of the neuron-glial interactions in the aged brain will disclose novel strategies to handle healthy cognitive aging in humans.